2009
DOI: 10.1016/j.neuroscience.2008.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of α1-adrenoceptors reduces glutamatergic synaptic input from primary afferents through GABAA receptors and T-type Ca2+ channels

Abstract: Activation of the descending noradrenergic system inhibits nociceptive transmission in the spinal cord. Although both α 1 -and α 2 -adrenoceptors in the spinal cord are involved in the modulation of nociceptive transmission, it is not clear how α 1 -adrenoceptors regulate excitatory and inhibitory synaptic transmission at the spinal level. In this study, inhibitory and excitatory postsynaptic currents (IPSCs and EPSCs, respectively) were recorded from lamina Π neurons in rat spinal cord slices. The specific α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 56 publications
(89 reference statements)
0
32
0
Order By: Relevance
“…Presynaptic GABA A receptor activation, which is produced by the release of GABA from spinal interneurons, inhibits glutamatergic input from primary afferents to dorsal horn neurons (Yuan et al, 2009). In this study, we demonstrated that nerve injury induced a depolarizing shift of E GABA in DRG neurons and that intrathecal KCC2 gene transfer completely reversed this depolarizing shift.…”
Section: Discussionmentioning
confidence: 99%
“…Presynaptic GABA A receptor activation, which is produced by the release of GABA from spinal interneurons, inhibits glutamatergic input from primary afferents to dorsal horn neurons (Yuan et al, 2009). In this study, we demonstrated that nerve injury induced a depolarizing shift of E GABA in DRG neurons and that intrathecal KCC2 gene transfer completely reversed this depolarizing shift.…”
Section: Discussionmentioning
confidence: 99%
“…Presynaptic α1-ARs’ activation mediates inhibition of GABA-releasing cells in rat hippocampal cultures, auditory cortex, cerebellum and spinal dorsal horn neurons (Mouradian et al, 1991, Croce et al, 2003, Yuan et al, 2009, Salgado et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, facilitation of rat spinal motoneuron activity [145] and of vasopressin release [146] are reported to be mediated by a1-adrenoceptors. a1-Adrenoceptor activation stimulates inhibitory GABAergic neurotransmission in rat spinal cord [147], rat cerebellum [148], mouse accessory olfactory bulb [149] and mouse hypothalamus [150]. The a1-adrenoceptor-mediated facilitation may involve protein kinase C and increases in intracellular calcium [146,148,151].…”
Section: A1-adrenoceptor-mediated Inhibitionmentioning
confidence: 99%